Neuropsychiatric syndromes in patients with systemic lupus erythematosus and primary Sjögren syndrome: a comparative population-based study. Issue 10 (17th October 2008) - Harboe, E; Tjensvoll, A B; Maroni, S; Gøransson, L G; Greve, O J; Beyer, M K; Herigstad, A; Kvaløy, J T; Omdal, R
Abstract : Objectives: To compare the prevalence and pattern of neuropsychiatric (NP) syndromes observed in systemic lupus erythematosus (SLE) to patients with Primary Sjögren syndrome (PSS) using the American College of Rheumatology (ACR) criteria for the 19 NP syndromes seen in SLE. Methods: A population-based study was conducted including 68 patients with SLE (mean (SD) age 43.8 (13.6) years) and 72 with PSS (age 57.8 (13.0) years). Specialists in internal medicine, neurology and neuropsychology performed standardised examinations. Cerebral MRI scans and neurophysiological studies were performed in all patients. Results: Similar prevalences in SLE and PSS were observed for headaches (87% vs 78%, p = 0.165), cognitive dysfunction (46% vs 50%, p = 0.273), mood disorders (26% vs 33%, p = 0.376), anxiety disorders (12% vs 4%, p = 0.095), cranial neuropathy (1% vs 4%, p = 0.339) and seizure disorders (7% vs 3%, p = 0.208). Cerebrovascular disease was more common in SLE than PSS (12% vs 3%, p = 0.049); but mononeuropathy (0% vs 8%, p = 0.015) and polyneuropathy (18% vs 56%, p<0.001) were less common in SLE than PSS. Other syndromes were rare or absent in both patient groups. Conclusions: Headache, cognitive dysfunction and mood disorders are common in both diseases, but otherwise there are distinct differences in NP involvement, with cerebrovascular diseases more prevalent in SLE and neuropathies more common in PSS. This indicates that some NP disease mechanisms are shared while others differ between the two diseases.